Respuesta :

Answer:

x = 2

y = -1

Step-by-step explanation:

x² + y = 3      --------------------(i)

x² = 3 - y

x² - y = 5 ---------------------(ii)

substitute x² = 3 - y in equation (ii)

x² - y = 5

3 - y -y = 5        {Add like terms}

3 - 2y = 5              {Subtract 3 from both sides}

3 - 2y -3 = 5 - 3

-2y = 2             {divide both sides by -2}

-2y/-2 = 2/-2

y = -1

Substitute the value of y in equation (i)

x² + y = 3

x² - 1= 3         {Add  1 to both sides}

x² - 1 + 1 = 3+ 1

x² = 4

x = √4

x = 2

ACCESS MORE